2021
DOI: 10.1089/g4h.2020.0028
|View full text |Cite|
|
Sign up to set email alerts
|

The Effect of Adding Virtual Reality Training on Traditional Exercise Program on Balance and Gait in Unilateral, Traumatic Lower Limb Amputee

Abstract: Objective: Lower limb amputation is common in war combat and armed conflict as well as in traumatic settings and presents a challenge for health care providers. The incorporation of advanced technologies, particularly virtual reality, presents an opportunity to address the main consequences of amputation, principally balance and gait. The aim of this study was to investigate the additional effect of virtual reality with a traditional rehabilitation exercise program on balance and gait in unilateral, traumatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 33 publications
0
37
0
Order By: Relevance
“…This group of keywords containing 11 items addresses the flexibility of VR in addition to conventional rehabilitation programs [ 49 , 50 ], and the possibility of expanding the reach of treatments beyond clinically controlled settings to achieve better results [ 22 ]. In addition, this cluster includes the adaption of VR games detached from any clinical setting and found the VR games had a positive effect on patient rehabilitation comparable to trainings conducted by medical professionals [ 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…This group of keywords containing 11 items addresses the flexibility of VR in addition to conventional rehabilitation programs [ 49 , 50 ], and the possibility of expanding the reach of treatments beyond clinically controlled settings to achieve better results [ 22 ]. In addition, this cluster includes the adaption of VR games detached from any clinical setting and found the VR games had a positive effect on patient rehabilitation comparable to trainings conducted by medical professionals [ 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, considering that amputees have no neurological injury, using the appropriate accommodations, the use of a tool such as a balance board can be important to stimulate the proprioceptive afferences and produce learning of new postural skills, as was demonstrated for healthy individuals [ 43 , 44 ]. Moreover, recent studies have demonstrated that the use of new tools, such as motor imagery [ 19 , 45 ] and virtual reality [ 46 ], can provide an important support in training and monitoring the development and updating of internal models, in subjects with a lower limb amputation.…”
Section: Conclusion and Practical Implicationsmentioning
confidence: 99%
“…Hwang et al discussed the effects of virtual reality-based upper limb rehabilitation training on upper limb function, muscle activity, daily living activities, and quality of life of stroke patients [ 7 ]. Abbas et al discussed the effect of graded motor rehabilitation and cognitive function training supported by virtual reality (VR) technology on the efficacy of patients with CHF complicated with cognitive impairment [ 9 ]. Soufi Ahmadi et al discussed the application of virtual reality technology in balance function rehabilitation training teaching, providing references and suggestions for using virtual reality technology in balance function rehabilitation training teaching [ 10 ].…”
Section: Introductionmentioning
confidence: 99%